A method for preparing a high dielectric polymer, a high dielectric film and a method for preparing the same

By introducing nylon 1 in two steps, combining crosslinking reaction and urea polycondensation, the problem of the decrease in flexibility and breakdown strength after nylon 1 and polyvinylidene fluoride is solved, and the preparation of high dielectric polymer is achieved, with good flexibility and breakdown strength, suitable for non-flat surface environments.

CN119463388BActive Publication Date: 2025-04-08DUJIANGYAN TIANXING SILICON IND CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510045093.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-08
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

In the prior art, nylon 1 and polyvinylidene fluoride compound lead to a decrease in flexibility and breakdown strength, especially in the use environment of non-flat surfaces.

Method used

By introducing nylon 1 in two steps, firstly, nylon 1 is crosslinked with polyvinylidene fluoride through crosslinking reaction, the reaction conditions and raw material ratio are adjusted to reduce the crosslinking degree and the proportion of nylon 1; secondly, nylon 1 is interspersed into the network structure of the composite through urea polycondensation to ensure its compatibility and dielectric properties.

Benefits of technology

It improves the flexibility and breakdown strength of the product, ensures that high performance can be maintained in non-flat surface use environments, and through the use of supercritical carbon dioxide, uniform dispersion of urea and high polymerization of nylon 1 are achieved, further improving dielectric performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463388B_ABST
    Figure CN119463388B_ABST
Patent Text Reader

Abstract

The invention relates to the field of dielectric materials. In order to solve the problem that nylon 1 and polyvinylidene fluoride are compounded to reduce flexibility and breakdown strength in the prior art, a method for preparing a high dielectric polymer, a high dielectric film and a preparation method thereof are provided. The method for preparing the high dielectric polymer comprises: S100, cross-linking 5-8 parts of nylon 1 and 120-150 parts of polyvinylidene fluoride to obtain a nylon 1 / polyvinylidene fluoride composite; the reaction temperature is 100-130°C, and the reaction time is 8-12 minutes; S200, adding 15-25 parts of urea, 200-230 parts of nylon 1 / polyvinylidene fluoride composite and 0.1-0.3 parts of auxiliary agent into a container, and then introducing carbon dioxide to make the carbon dioxide in a supercritical state; S300, performing polycondensation reaction; S400, adding a capping agent, and finally obtaining a high dielectric polymer. The preparation method of the high dielectric polymer provided by the present invention ensures the compatibility between nylon 1 and polyvinylidene fluoride by introducing nylon 1 in two steps, reduces the cross-linking degree of the product, and improves the flexibility of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of dielectric materials, and in particular to a method for preparing a high dielectric polymer, a high dielectric film and a method for preparing the same. Background Art

[0002] As a high-performance fluorinated polymer, polyvinylidene fluoride has shown wide application potential in the field of dielectric film materials due to its unique dielectric properties and mechanical characteristics. However, the performance of polyvinylidene fluoride alone is no longer suitable for the current rapid development of electronic information technology. Currently, adding functional fillers to polyvinylidene fluoride to improve its performance is one of the common technologies.

[0003] The patent with publication number CN111849093A discloses a nylon 1 / polyvinylidene fluoride composite dielectric film and a preparation method thereof, wherein nylon 1 and polyvinylidene fluoride are composited by a cross-linking reaction, which not only improves the dielectric properties of polyvinylidene fluoride, but also makes nylon 1 and polyvinylidene fluoride have good compatibility, thereby solving the problems of high dielectric loss, easy agglomeration of fillers, and reduced breakdown strength when the prior art blends and modifies polyvinylidene fluoride with inorganic fillers having high dielectric constants. However, the cross-linking structure of the two substances affects the flexibility of the dielectric film product, which limits its use in some non-flat surface environments. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a high dielectric polymer, so as to solve the problem in the prior art that the flexibility and breakdown strength decrease after nylon 1 is compounded with polyvinylidene fluoride.

[0005] Another object of the present invention is to provide a high dielectric film and a method for preparing the same, which can maintain a high breakdown strength even in a non-planar surface usage environment.

[0006] The embodiments of the present invention are implemented by the following technical solutions:

[0007] A method for preparing a high dielectric polymer, comprising:

[0008] S100, by weight, 5-8 parts of nylon 1 and 120-150 parts of polyvinylidene fluoride are cross-linked to obtain a nylon 1 / polyvinylidene fluoride composite; the reaction temperature is 100-130° C., and the reaction time is 8-12 minutes;

[0009] S200, after adding 15-25 parts of urea, 200-230 parts of nylon 1 / polyvinylidene fluoride composite and 0.1-0.3 parts of auxiliary agent in parts by weight into a container, the air in the container is removed, the temperature is increased and carbon dioxide is introduced to make the carbon dioxide in a supercritical state;

[0010] S300, regulating the reaction to perform a polycondensation reaction;

[0011] S400, after the polycondensation reaction is completed, a capping agent is added to carry out a capping reaction, and finally a high dielectric polymer is obtained.

[0012] On April 26, 2019, the applicant applied for a patent with publication number CN111849093A, which disclosed a nylon 1 / polyvinylidene fluoride composite dielectric film and its preparation method. It composites nylon 1 with polyvinylidene fluoride through a cross-linking reaction, which not only improves the dielectric properties of polyvinylidene fluoride, but also makes nylon 1 and polyvinylidene fluoride have good compatibility, and solves the problems of high dielectric loss, easy agglomeration of fillers, and reduced breakdown strength when the existing technology is modified by blending high dielectric constant inorganic fillers with polyvinylidene fluoride. However, the cross-linked structure of the two substances affects the flexibility of the dielectric film product, which limits its use in some non-flat surfaces. Therefore, the applicant hopes to further improve the flexibility of the product, especially low-temperature flexibility, on the basis of modifying polyvinylidene fluoride through nylon 1. In addition, due to the reduced dispersion ability of the electric field breakdown stress, the breakdown strength also decreases to a certain extent.

[0013] The cross-linking reaction in S100 can refer to the above patent. The present invention introduces nylon 1 into the polyvinylidene fluoride structure in two steps. First, as in the above patent, nylon 1 and polyvinylidene fluoride are cross-linked through a cross-linking reaction, but the reaction conditions and raw material ratios are adjusted to reduce the cross-linking degree of the composite and the proportion of nylon 1. The reason for the treatment is that after the two-step introduction, the proportion of nylon can be compensated by the second introduction, and the reduction of nylon 1 reduces the required cross-linking points, which can reduce the degree of cross-linking and ensure flexibility as much as possible. The second introduction is to allow the linear structure of nylon 1 to be interspersed in the network structure of the composite through urea condensation without cross-linking, which can not only improve the dielectric properties of the product through nylon 1, but also ensure its flexibility. One of the reasons why the present invention introduces nylon 1 in two steps is that: if nylon 1 is directly introduced into the cross-linked polyvinylidene fluoride structure through the operation in S200, such as some modified polyvinylidene fluoride, the compatibility between nylon 1 and polyvinylidene fluoride decreases relative to direct cross-linking, which violates the original intention of the aforementioned patent, and after introducing nylon 1 once to obtain a composite, nylon 1 is introduced twice with the composite as a matrix, which can improve the compatibility between the secondary introduced nylon 1 and the polymer. In addition, by adjusting the reaction parameters, regulating the degree of polymerization of nylon 1 can further increase the compatibility between polymers. Too low a polymerization degree of nylon 1 will affect its dielectric properties, while too high a polymerization degree will limit the mobility of the polymer long chain, so the regulation of the reaction parameters needs to take into account the dielectric properties, compatibility, product flexibility and the diffusivity of supercritical carbon dioxide, etc.

[0014] Although the nylon 1 with high polymerization degree in the present invention brings more excellent dielectric properties to the film, its viscosity is high. In the composite process of S300, the dispersibility of the composite and urea is poor, which can significantly affect the dielectric properties of the final product. Thus the present invention also utilizes the high diffusivity of supercritical carbon dioxide in the polymer system, so that the urea monomer can be better evenly dispersed and enter the composite structure, improves the uniformity of the filler, and then improves the breakdown strength of the product. From the above, it can be seen that after using supercritical carbon dioxide, the problem of poor dispersibility caused by the excessive polymerization of nylon 1 can be reduced, and then the polymerization degree of nylon 1 in the film can be improved, and the dielectric properties of the film can be improved. In addition, the chain segment of nylon 1 is longer, compared with the short chain interspersed in the composite structure, the tensile strength, compressive strength and thermal stability of the overall structure increase. The increase in thermal stability can further improve the breakdown strength of the film. The hydrogen bond between nylon 1 molecules can reduce the spacing between the molecular chains, reducing the jumping spacing of the carriers.

[0015] Preferably, the S300 includes:

[0016] A100, adjust the reaction parameters to carry out a polycondensation reaction, the reaction pressure is 18-23MPa, the reaction temperature is 120-150℃, and the reaction time is 5-8h;

[0017] A200, adjust the reaction parameters to carry out secondary polycondensation reaction, the reaction pressure is 10-15MPa, the reaction temperature is 180-240℃, and the reaction time is 2-4h.

[0018] The reason why the present invention adopts two polycondensation reactions is that: during a polycondensation reaction, the system material structure is constantly changing, and the ability of supercritical carbon dioxide to swell polymers is getting lower and lower, thus in a polycondensation, first adopt the reaction conditions for the current system material, when the polycondensation reaction proceeds to a certain extent, then adjust the reaction parameters, so that the reaction conditions are adapted to the system material of the current high degree of polymerization, the time required for the reaction can be greatly reduced, and the raw material conversion rate is improved. Due to the difference between the solubility curve of the complex and urea in carbon dioxide, it is difficult to meet the two simultaneously and both have good solubility, and in a single reaction, the solubility of the complex is used as a benchmark, to improve the dispersibility of urea, and it is convenient for the interlacing of the polycondensation product in the complex structure. However, as the polycondensation proceeds, the solubility of the polymer is reduced, and swelling is weakened, and the solubility difference between urea and the polymer increases, and the good dispersibility of urea between the polymer structure is met, then the conversion rate of urea can be reduced, and thus the secondary polycondensation in the present invention is based on the urea conversion rate, and the reaction conditions are regulated. During the first polycondensation, the maximum degree of polymerization that nylon 1 can achieve is controlled, mainly by inserting short-chain nylon 1 in the composite structure. During the second polycondensation, the maximum degree of polymerization that nylon 1 can achieve is increased, mainly by increasing the length of the short chain. Since the reaction system is high temperature and high pressure, if the two polycondensation reactions are achieved by batch feeding, the energy consumption will increase. In addition, during the first polycondensation reaction, stirring can also be used to increase the uniformity of the system.

[0019] Preferably, when the reaction parameters are changed from the conditions of the primary polycondensation reaction to the conditions of the secondary polycondensation reaction, the heating rate is 10-20° C. / min.

[0020] In order to avoid chain termination during the heating process, which would lead to failure of chain growth in the secondary polycondensation reaction, the heating rate is controlled in the present invention.

[0021] Preferably, the molecular weight of the polyvinylidene fluoride in the S100 is 300,000-400,000, and the average degree of polymerization of nylon 1 is 50-80.

[0022] In order to reduce heat concentration, improve the thermal stability of the product, and then improve the breakdown strength, the present invention selects polyvinylidene fluoride of appropriate molecular weight to cooperate with polycondensation reaction to control the polymerization degree of nylon 1, so that the difference in thermal conductivity between the two is reduced. In addition, during the mixing of polyvinylidene fluoride and nylon 1, the mixing uniformity has a greater impact on the performance of the product, so when nylon 1 is introduced once, nylon 1 with a relatively low polymerization degree is used. When introduced for the second time, nylon 1 with a high polymerization degree is obtained by polycondensation reaction.

[0023] Preferably, the S300 further comprises: after the polycondensation reaction is completed, lowering the temperature in the container to 31.1-40°C, then adding starch crystals, the mass ratio of starch crystals to urea being 1:50-1:30, introducing carbon dioxide again until the pressure in the container is 9-12Mpa, stirring for 2-5 minutes, and then rapidly releasing the pressure.

[0024] Since the breakdown strength is also related to the thickness of the polymer film, in theory, the thicker the film, the higher the breakdown strength, but when the polymer film is applied to a non-planar environment, the thicker the film, the more severe the stress concentration at the bend, and stress concentration may cause changes in the molecular chain structure. For example, in the process of polymer film processing, the calendering process may also cause structural defects in the polymer, causing the charge to be more easily accumulated in the stress concentration area, accompanied by an increase in the local electric field, which will increase the risk of breakdown in the area. Although the present invention improves the tensile strength of the material to a certain extent and reduces the influence of stress on the molecular chain structure by inserting long-chain nylon 1 in the composite structure, the applicant expects to further reduce the structural defects caused by stress or stress concentration, break through the maximum thickness of the polymer film under the same curvature environment, so as to be suitable for some special-shaped components, thus the present invention utilizes the pressure relief process of the supercritical carbon dioxide system to form micropores inside the polymer, and the porosity and micropore diameter can be adjusted by regulating the pressure relief process. The presence of micropores can disperse stress and reduce the reduction of dielectric properties caused by stress concentration, but the dielectric constant of gas in micropores is low, and the presence of gas will reduce the dielectric constant of polymer. Under the combined influence of the two, the dielectric properties of polymer film may increase or decrease. The applicant obtained the pore-forming process provided by the present invention after the experiment. Both feeding and temperature drop lead to a decrease in pressure in the container. In order to ensure that the pressure meets the pore-forming requirements, the present invention introduces carbon dioxide again.

[0025] In addition, since the presence of pores will reduce the dielectric constant of the polymer film in the horizontal state, the experiment of the present invention is mainly aimed at application scenarios with a low plane ratio. When the plane ratio does not exceed 20% and the maximum curvature does not exceed 10, a large number of polymer films are bent. Assuming that the breakdown voltage of the plane area is a1 and the breakdown voltage of the area with maximum curvature is a2, the optimal process parameters are obtained based on the size of the M value, M=0.2a1+0.8a2.

[0026] Preferably, the pressure relief operation includes: firstly releasing the pressure in the container to 5-7 MPa for 4-6 hours, then maintaining the pressure for 1-2 hours, and finally reducing the pressure in the container to atmospheric pressure for 5-8 seconds.

[0027] Preferably, the blocking agent includes: one or more of maleic anhydride, ethanol and hexamethylene diisocyanate.

[0028] By selecting appropriate end-capping agents, the chemical structure of the ends of nylon molecular chains can be effectively controlled, thus significantly affecting its physical, mechanical and thermal properties.

[0029] A method for preparing a high dielectric film includes the method for preparing the high dielectric polymer, wherein S100 includes: mixing polyvinylidene fluoride and nylon 1 according to a ratio, kneading at 180-200° C. for 10-20 minutes, then hot pressing the kneaded product at 100-130° C. for 8-12 minutes, and then maintaining the pressure at room temperature for 8-12 minutes to obtain a nylon 1 / polyvinylidene fluoride composite film with a thickness of 1-300 μm.

[0030] The present invention has at least the following beneficial effects:

[0031] The preparation method of the high dielectric polymer provided by the present invention introduces nylon 1 in two steps, thereby ensuring the compatibility between nylon 1 and polyvinylidene fluoride, reducing the cross-linking degree of the product, and improving the flexibility of the product; using supercritical carbon dioxide not only realizes the polycondensation reaction of urea, but also improves the uniformity of nylon 1 in the product, further improving the dielectric properties of the product, and in addition, using supercritical carbon dioxide to prepare a microporous membrane, so that it can be better applied to special-shaped components; the chain segment of nylon 1 is longer, and compared with short chains interspersed in the composite structure, the tensile strength, compressive strength and thermal stability of the overall structure are increased. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0033] Figure 1 The dielectric constant curves of the dielectric films prepared by the preparation methods provided in Examples 1-5 and the blank examples are shown;

[0034] Figure 2 The dielectric constant curves of the dielectric films prepared by the preparation methods provided in Example 3 and Comparative Examples 1-5 are shown;

[0035] Figure 3 This is a schematic diagram of the structure of the special-shaped component used in Experiment 2. DETAILED DESCRIPTION

[0036] In order to make the purpose, method scheme and advantages of the embodiments of the present invention clearer, the method scheme in the embodiments of the present invention is clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0037] Embodiment 1: A method for preparing a high dielectric polymer, comprising, by weight:

[0038] S100, in parts by weight, 5 parts of nylon 1 and 120 parts of polyvinylidene fluoride were mixed, and kneaded on a torque rheometer at 180° C. for 10 minutes, and then the kneaded product was hot-pressed at 100° C. for 8 minutes, and then kept at room temperature for 8 minutes to obtain a nylon 1 / polyvinylidene fluoride composite; the molecular weight of the polyvinylidene fluoride was 300,000, and the average degree of polymerization of nylon 1 was 50;

[0039] S200, after adding 15 parts of urea, 200 parts of nylon 1 / polyvinylidene fluoride composite and 0.1 parts of zinc carbonate in parts by weight into a container, the air in the container is removed, the temperature is increased and carbon dioxide is introduced to make the carbon dioxide in a supercritical state;

[0040] S300, including:

[0041] A100, adjusting the reaction parameters to carry out a polycondensation reaction, the reaction pressure is 18MPa, the reaction temperature is 100℃, and the reaction time is 5h;

[0042] A200, adjust the reaction parameters for secondary polycondensation reaction, the reaction pressure is 10MPa, the reaction temperature is 180℃, and the reaction time is 2h;

[0043] When the reaction parameters are changed from the conditions of the primary polycondensation reaction to the conditions of the secondary polycondensation reaction, the heating rate is 10°C / min;

[0044] After the polycondensation reaction is completed, the temperature in the container is lowered to 31.1°C, and then starch crystals are added, with the mass ratio of starch crystals to urea being 1:50. Carbon dioxide is introduced again until the pressure in the container reaches 9 MPa. After stirring for 2 minutes, the pressure is released;

[0045] The pressure relief operation includes: firstly releasing the pressure in the container to 5Mpa for 4 hours, then maintaining the pressure for 1 hour, and finally reducing the pressure in the container to atmospheric pressure for 5 seconds;

[0046] S400, after the polycondensation reaction is completed, hexamethylene diisocyanate is added to carry out a capping reaction. The temperature of the capping reaction is 180° C., the time is 15 minutes, and the weight ratio of hexamethylene diisocyanate to urea is 1:200, and finally a high dielectric polymer is obtained.

[0047] Embodiment 2: A method for preparing a high dielectric polymer, comprising, by weight:

[0048] S100, in parts by weight, 8 parts of nylon 1 and 150 parts of polyvinylidene fluoride were mixed, and kneaded on a torque rheometer at 200° C. for 20 minutes, and then the mixed product was hot-pressed at 130° C. for 12 minutes, and then kept at room temperature for 12 minutes to obtain a nylon 1 / polyvinylidene fluoride composite; the molecular weight of the polyvinylidene fluoride was 400,000, and the average degree of polymerization of nylon 1 was 80;

[0049] S200, after adding 25 parts of urea, 230 parts of nylon 1 / polyvinylidene fluoride composite and 0.3 parts of zinc carbonate in parts by weight into a container, the air in the container is removed, the temperature is increased and carbon dioxide is introduced to make the carbon dioxide in a supercritical state;

[0050] S300, including:

[0051] A100, adjusting the reaction parameters to carry out a polycondensation reaction, the reaction pressure is 23MPa, the reaction temperature is 140℃, and the reaction time is 8h;

[0052] A200, adjust the reaction parameters for secondary polycondensation reaction, the reaction pressure is 15MPa, the reaction temperature is 240℃, and the reaction time is 4h;

[0053] When the reaction parameters are changed from the conditions of the primary polycondensation reaction to the conditions of the secondary polycondensation reaction, the heating rate is 20°C / min;

[0054] After the polycondensation reaction is completed, the temperature in the container is lowered to 40°C, and then starch crystals are added, with the mass ratio of starch crystals to urea being 1:30. Carbon dioxide is introduced again until the pressure in the container reaches 12 MPa. After stirring for 5 minutes, the pressure is released;

[0055] The pressure relief operation includes: firstly releasing the pressure in the container to 7Mpa for 6 hours, then maintaining the pressure for 2 hours, and finally reducing the pressure in the container to atmospheric pressure for 8 seconds;

[0056] S400, after the polycondensation reaction is completed, hexamethylene diisocyanate is added to carry out a capping reaction. The temperature of the capping reaction is 200° C., the time is 20 min, and the weight ratio of hexamethylene diisocyanate to urea is 3:100, and finally a high dielectric polymer is obtained.

[0057] Embodiment 3: A method for preparing a high dielectric polymer, comprising, by weight:

[0058] S100, in parts by weight, 7 parts of nylon 1 and 140 parts of polyvinylidene fluoride were mixed, and kneaded on a torque rheometer at 190° C. for 15 minutes, and then the kneaded product was hot-pressed at 120° C. for 10 minutes, and then kept at room temperature for 10 minutes to obtain a nylon 1 / polyvinylidene fluoride composite; the molecular weight of the polyvinylidene fluoride was 350,000, and the average degree of polymerization of nylon 1 was 70;

[0059] S200, after adding 20 parts of urea, 220 parts of nylon 1 / polyvinylidene fluoride composite and 0.2 parts of zinc carbonate in parts by weight into a container, the air in the container is removed, the temperature is increased and carbon dioxide is introduced to make the carbon dioxide in a supercritical state;

[0060] S300, including:

[0061] A100, adjusting the reaction parameters to carry out a polycondensation reaction, the reaction pressure is 21MPa, the reaction temperature is 120℃, and the reaction time is 7h;

[0062] A200, adjust the reaction parameters for secondary polycondensation reaction, the reaction pressure is 12MPa, the reaction temperature is 210℃, and the reaction time is 3h;

[0063] When the reaction parameters are changed from the conditions of the primary polycondensation reaction to the conditions of the secondary polycondensation reaction, the heating rate is 15°C / min;

[0064] After the polycondensation reaction is completed, the temperature in the container is lowered to 35°C, and then starch crystals are added, the mass ratio of starch crystals to urea is 1:40, and carbon dioxide is introduced again until the pressure in the container reaches 10Mpa. After stirring for 3 minutes, the pressure is released;

[0065] The pressure relief operation includes: firstly releasing the pressure in the container to 6Mpa for 5 hours, then maintaining the pressure for 1.5 hours, and finally reducing the pressure in the container to atmospheric pressure for 6 seconds;

[0066] S400, after the polycondensation reaction is completed, hexamethylene diisocyanate is added to carry out a capping reaction. The temperature of the capping reaction is 190° C., the time is 18 min, and the weight ratio of hexamethylene diisocyanate to urea is 1:50, and finally a high dielectric polymer is obtained.

[0067] Embodiment 4: A method for preparing a high dielectric polymer, comprising, by weight:

[0068] S100, in parts by weight, 7 parts of nylon 1 and 140 parts of polyvinylidene fluoride were mixed, and kneaded on a torque rheometer at 190° C. for 15 minutes, and then the kneaded product was hot-pressed at 120° C. for 10 minutes, and then kept at room temperature for 10 minutes to obtain a nylon 1 / polyvinylidene fluoride composite; the molecular weight of the polyvinylidene fluoride was 350,000, and the average degree of polymerization of nylon 1 was 70;

[0069] S200, after adding 20 parts of urea, 220 parts of nylon 1 / polyvinylidene fluoride composite and 0.2 parts of zinc carbonate in parts by weight into a container, the air in the container is removed, the temperature is increased and carbon dioxide is introduced to make the carbon dioxide in a supercritical state;

[0070] S300, including:

[0071] A100, adjusting the reaction parameters to carry out a polycondensation reaction, the reaction pressure is 21MPa, the reaction temperature is 120℃, and the reaction time is 7h;

[0072] A200, adjust the reaction parameters for secondary polycondensation reaction, the reaction pressure is 12MPa, the reaction temperature is 210℃, and the reaction time is 3h;

[0073] When the reaction parameters are changed from the conditions of the primary polycondensation reaction to the conditions of the secondary polycondensation reaction, the heating rate is 15°C / min;

[0074] After the polycondensation reaction is completed, the temperature in the container is lowered to 35°C, and then starch crystals are added, the mass ratio of starch crystals to urea is 1:40, and carbon dioxide is introduced again until the pressure in the container reaches 10Mpa. After stirring for 3 minutes, the pressure is released;

[0075] The pressure relief operation includes: firstly releasing the pressure in the container to 6Mpa for 5 hours, then maintaining the pressure for 1.5 hours, and finally reducing the pressure in the container to atmospheric pressure for 6 seconds;

[0076] S400, after the polycondensation reaction is completed, maleic anhydride is added to carry out a capping reaction. The temperature of the capping reaction is 190° C., the time is 18 minutes, and the weight ratio of maleic anhydride to urea is 1:50, and finally a high dielectric polymer is obtained.

[0077] Example 5: A method for preparing a high dielectric polymer, comprising, by weight:

[0078] S100, in parts by weight, 7 parts of nylon 1 and 140 parts of polyvinylidene fluoride were mixed, and kneaded on a torque rheometer at 190° C. for 15 minutes, and then the kneaded product was hot-pressed at 120° C. for 10 minutes, and then kept at room temperature for 10 minutes to obtain a nylon 1 / polyvinylidene fluoride composite; the molecular weight of the polyvinylidene fluoride was 350,000, and the average degree of polymerization of nylon 1 was 70;

[0079] S200, after adding 20 parts of urea, 220 parts of nylon 1 / polyvinylidene fluoride composite and 0.2 parts of zinc carbonate in parts by weight into a container, the air in the container is removed, the temperature is increased and carbon dioxide is introduced to make the carbon dioxide in a supercritical state;

[0080] S300, including:

[0081] A100, adjusting the reaction parameters to carry out a polycondensation reaction, the reaction pressure is 21MPa, the reaction temperature is 120℃, and the reaction time is 7h;

[0082] A200, adjust the reaction parameters for secondary polycondensation reaction, the reaction pressure is 12MPa, the reaction temperature is 210℃, and the reaction time is 3h;

[0083] When the reaction parameters are changed from the conditions of the primary polycondensation reaction to the conditions of the secondary polycondensation reaction, the heating rate is 15°C / min;

[0084] After the polycondensation reaction is completed, the temperature in the container is lowered to 35°C, and then starch crystals are added, the mass ratio of starch crystals to urea is 1:40, and carbon dioxide is introduced again until the pressure in the container reaches 10Mpa. After stirring for 3 minutes, the pressure is released;

[0085] The pressure relief operation includes: firstly releasing the pressure in the container to 6Mpa for 5 hours, then maintaining the pressure for 1.5 hours, and finally reducing the pressure in the container to atmospheric pressure for 6 seconds;

[0086] S400, after the polycondensation reaction is completed, ethanol is added to carry out a capping reaction. The temperature of the capping reaction is 190°C, the time is 18 minutes, and the weight ratio of ethanol is 1:50, and finally a high dielectric polymer is obtained.

[0087] Comparative Example 1: The difference from Example 3 is that, like the patent with application number 201711448265.8, S300 adopts a single polycondensation, the reaction pressure is 12Mpa, the reaction temperature is 145°C, and the reaction time is 7h.

[0088] Comparative Example 2: The difference from Example 3 is that the average polymerization degree of nylon 1 in S100 is 200.

[0089] Comparative Example 3: The difference from Example 3 is that the pressure relief operation is a quick pressure relief, and the pressure relief time is 20s.

[0090] Comparative Example 4: The difference from Example 3 is that when the reaction parameters are changed from the conditions of the primary polycondensation reaction to the conditions of the secondary polycondensation reaction, the heating rate is 30°C / min.

[0091] Comparative Example 5: The difference from Example 3 is that the mixed product is hot-pressed at 180° C. for 15 min and then kept at room temperature for 5 min to obtain a nylon 1 / polyvinylidene fluoride composite.

[0092] Blank example: polyvinylidene fluoride film.

[0093] Test 1: The dielectric constant of the high dielectric films (thickness 200 μm) prepared by the preparation methods of Examples 1-5 and Comparative Examples 1-5 and the blank samples were tested. The test results are shown in Figure 1-2 .

[0094] from Figure 1It can be seen that the high dielectric constant film prepared by the preparation method provided by the present invention has a relatively high dielectric constant. Among them, the film prepared by the preparation method provided by Example 3 has the best performance.

[0095] from Figure 2 It can be seen that the performance of the film prepared by the preparation method provided in Example 3 and Comparative Example 3 is better than that of the other comparative examples. When the application scenario is a plane, the preparation method provided in Example 3 or Comparative Example 3 can be adopted.

[0096] Experiment 2: The high dielectric films (thickness of 200 μm) prepared according to the preparation methods of Examples 1-5 and Comparative Examples 1-5 and the blank samples were subjected to breakdown strength tests. The test method is as follows:

[0097] Glue the film to Figure 3 The outer surface of the special-shaped component shown in the figure has a maximum curvature of 10 and a plane area of ​​20% of the total area. The breakdown voltage is then tested using a dielectric breakdown strength tester. Five points are selected on the curved surface and the plane to test the breakdown voltage and the average value is taken. Assuming that the breakdown voltage of the plane area is a1 and the breakdown voltage of the area with the maximum curvature is a2, M=0.2a1+0.8a2 is calculated, and the breakdown strength E=M / d, where d is the film thickness and the unit of breakdown strength is MV / m. The test results are shown in Table 1.

[0098] Table 1

[0099] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 E 367.1 382.6 402.7 386.4 391.8 306.7 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Blank example E 312.3 309.5 341.2 337.8 241.4

[0100] From the results of Examples 1-5 in Table 1, it can be seen that the high dielectric film prepared by the preparation method provided by the present invention has a relatively high breakdown strength.

[0101] From the comparison between Example 3 and Comparative Examples 1-5, it can be seen that after the preparation method provided in Example 3 is used, the breakdown strength of the high dielectric film is significantly enhanced.

[0102] From the comparison between Example 3 and Comparative Example 3, it can be seen that the high dielectric film prepared by the preparation method provided in Comparative Example 3 has worse performance than that of Example 3 when applied to components with higher curvature.

[0103] Test 3: The high dielectric films (thickness 200 μm) prepared according to the preparation methods of Examples 1-5 and Comparative Examples 1-5 and the blank samples were tested for tensile strength and tensile elongation at break. The test method is as follows:

[0104] Five specimens with a size of 50×250×4 mm were made of high dielectric film and tested using an MX-1080 tensile testing machine with a tensile speed of 50 mm / min and a test temperature of 2°C. The test results of tensile strength and elongation at break are shown in Table 2.

[0105] Table 2

[0106] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Tensile strength / MPa 42.6 45.1 47.3 45.9 46.0 31.7 Elongation at break / % 84.6 97.5 99.8 96.3 88.4 62.9 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Blank example Tensile strength / MPa 37.5 40.8 34.2 30.6 36.1 Elongation at break / % 67.6 75.4 57.0 54.3 61.7

[0107] From the test results of Examples 1-5, it can be seen that the high dielectric film prepared by the preparation method of the present invention has more excellent tensile properties and significantly increased flexibility. The performance of Comparative Example 1 and Comparative Examples 4-5 is even worse than that of the blank example.

[0108] From the comparison between Example 3 and Comparative Examples 1-5 and the blank example, it can be seen that the preparation method provided by the present invention can significantly improve the tensile properties of the film.

[0109] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high dielectric film, characterized in that: include: S100, by weight, 5-8 parts of nylon 1 and 120-150 parts of polyvinylidene fluoride are mixed, kneaded at 180-200° C. for 10-20 minutes, and then the kneaded product is hot-pressed at 100-130° C. for 8-12 minutes, and then kept at room temperature for 8-12 minutes to obtain a nylon 1 / polyvinylidene fluoride composite film with a thickness of 1-300 μm; the average degree of polymerization of nylon 1 is 50-80; S200, after adding 15-25 parts of urea, 200-230 parts of nylon 1 / polyvinylidene fluoride composite and 0.1-0.3 parts of auxiliary agent in parts by weight into a container, the air in the container is removed, the temperature is increased and carbon dioxide is introduced to make the carbon dioxide in a supercritical state; S300, regulating the reaction to perform a polycondensation reaction; S400, after the polycondensation reaction is completed, a capping agent is added to carry out a capping reaction, and finally a high dielectric polymer is obtained; The S300 includes: A100, adjusting the reaction parameters to carry out a polycondensation reaction, the reaction pressure is 18-23MPa, the reaction temperature is 100-140°C, and the reaction time is 5-8h; A200, adjust the reaction parameters for secondary polycondensation reaction, the reaction pressure is 10-15MPa, the reaction temperature is 180-240℃, and the reaction time is 2-4h; When the reaction parameters are changed from the conditions of the primary polycondensation reaction to the conditions of the secondary polycondensation reaction, the heating rate is 10-20°C / min; The S300 further includes: after the polycondensation reaction is completed, lowering the temperature in the container to 31.1-40° C., then adding starch crystals, wherein the mass ratio of starch crystals to urea is 1:50-1:30, introducing carbon dioxide again until the pressure in the container is 9-12 MPa, stirring for 2-5 minutes, and then performing a pressure relief operation; The pressure relief operation includes: firstly releasing the pressure in the container to 5-7Mpa for 4-6h, then maintaining the pressure for 1-2h, and finally reducing the pressure in the container to atmospheric pressure for 5-8s.

2. The preparation method according to claim 1, characterized in that: The molecular weight of the polyvinylidene fluoride in the S100 is 300,000-400,000.

3. The preparation method according to claim 1, characterized in that: The blocking agent includes one or more of maleic anhydride, ethanol and hexamethylene diisocyanate.

4. The preparation method according to claim 3, characterized in that: The temperature of the end-capping reaction is 180-200° C., the time is 15-20 minutes, and the weight ratio of the end-capping agent to urea is 1:200-3:

100.

5. A high dielectric film obtained by the preparation method according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Nylon 1, its preparation method and application

    CN109970973B

  • Nylon 1 / polyvinylidene fluoride composite dielectric film and preparation method thereof

    CN111849093A

  • Flexible polymer dielectric material for electrical condenser and preparation thereof

    CN101508841A

  • Preparation method of high-temperature-resisting fluorine-containing polymer cellular material

    CN103897309A